Productive Inclusion in Latin America : Policy and Operational Lessons - World Bank (World Bank, Washington, DC, 2020)
The dramatic transformation in Latin America and the Caribbean (LAC) between 2000 and the 2010s was driven by fast growth, together with higher employment rates and increased real incomes. During this period of sustained growth, increased fiscal revenues supported the expansion of social protection programs, mainly in the form of non-contributory social assistance. Despite the increasing coverage of social assistance and positive impacts on consumption and other social dimensions, policy makers were aware of the limitations in ensuring the sustainability of those gains. This report aims to document different approaches of productive inclusion (PI) in LAC countries, particularly focusing on the policy and implementation aspects, as well as the lessons learned from their design and implementation. The note is organized as follows. First, it presents the definition and an operational framework for productive inclusion, to provide a conceptual grounding for the analysis of different approaches observed in the region, identifying the key elements, from policy mandate-design to implementation. Next, common themes for successful PI interventions for each key pillar, are presented in turn, drawing from the rich information of the country case studies. The third section presents the experience and the challenges on the evaluation of PI programs in the region to date as well as a brief summary of the results. The note concludes with (operational) lessons learned to inform the evolution of the productive inclusion strategies for the low and middle-income countries in both LAC and other regions, and presents a brief overview of the pending issues on the agenda for the region for future research.